Noninvasive evaluation of the elasticity of common carotid artery wall - POWAŁOWSKI, T.; TRAWIŃSKI, Z. (Archives of Acoustics, 1994)
The elasticity of common carotid arteries was examined on the basis of noninvasive ultrasonic measurements of the diameter of the carotid artery and the systlic and diastolic pressures as determined by a cuff on the brachial artery. The measurements were performed for a group of 20 males, aged from 27 to 45 years. The examines were fighter plane pilots. The examinations were carried out for different systolic and diastolic pressures which were recorded along with measurements of the diameter of the carotid artery during rest, following an exercise test. This paper presents the results of measurements of the maximum and minimum diameters of the common carotid artery for different systolic and diastolic pressures in the brachial artery. Good coincidence was gained between the experimental results and the logarithmic function as described by POWAŁOWSKI. The coefficient of the determination R^2 fell between 0.993 and 0.999. On the basis of the results of the measurements of the artery diameter and the blood pressure, the values of coefficients describing the elastic properties of the common carotid arteries were defined. The investigated coefficients included: the elastic modulus E_p, the arterial distensibility coefficient DC, the cross-sectional compliance CC and the logarithmic stiffness coefficient α.